Chapter Преломление образа Фауста у Вячеслава Иванова - Di Leo, Donata (Biblioteca di Studi Slavistici, 2019)
In 1993 Michael Wachtel published Ivanov's Russian Faust, comprising two scenes that appear to continue Goethe's Faust and most likely represent the beginnings of a Faust drama. Ivanov was the first Russian poet to reevaluate the second part of Goethe's poem for its extremely symbolic content. As a result, he was considerably influenced by Goethe's creative experience. This article examines these two Faustian scenes and, more generally, the influence of Goethe's Faust in Ivanov's work; adopting a comparative approach, we explore the assimilation into Russian literature of a Central European myth.